The Effect of Blocked and Random Practice in Teaching Serve and Reception and setting of Volleyball - Saleh, Mohammed (Journal of Physical Education, 2010)
The purpose of this study was to know the effect of teaching (Blocked, Random, Blocked-Random, Traditional) of teaching some of skill Volleyball which is Serve and Reception and Setting discover the best to study to learning each of skill. The researcher has used the experimental approach of sample is made of (48) students from the second stage of the training part in the college of Physical Education – Baghdad University, 2008-2009. The sample has been divided into four groups of (12) students each. Each groups has one of condition of practice. The groups were homogenized in the effective Variable of the research. The premeasurement for the four groups were done by using mang objective tests and evaluation of agree from to define the accuracy performance of serve and receiving serve and setting. The program lasted for three month and included 12 training units, tow units a week. The pre-measurements were done immediately after the end of the program by using the same tests used in the pre-measurements.The statistical treatment were done. The results showed that there were significant statistical differences between the pre-test and post-test measurements on behalf on the for the use of post measurement for each groups. This effect because teach students for skills. The results also revealed that the Blocked practice the best practice of learn serve. Also the Blocked-Random practice is the best one practice of learn Reception and setting. The researcher recommended the importance of applying studies for learn the skills for defrend games especial volleyball game for make the study forming to good performance.